Age-Related Dynamics of Lung-Resident Memory CD8+ T Cells in the Age of COVID-19 - Goplen, Nick P.; Cheon, In Su; Sun, Jie (Frontiers in Immunology, 2021)
Following respiratory viral infections or local immunizations, lung resident-memory T cells (TRM) of the CD8 lineage provide protection against the same pathogen or related pathogens with cross-reactive T cell epitopes. Yet, it is now clear that, if homeostatic controls are lost following viral pneumonia, CD8 TRM cells can mediate pulmonary pathology. We recently showed that the aging process can result in loss of homeostatic controls on CD8 TRM in the respiratory tract. This may be of interest for treatment modalities in both influenza and coronavirus disease 2019 (COVID-19) patients, particularly, the portion that present with symptoms linked to long-lasting lung dysfunction. Here, we review the developmental cues and functionalities of CD8 TRM in viral pneumonia models with a particular focus on their capacity to mediate heterogeneous responses of immunity and pathology dependent on immune status.